Demographic Profile and Clinical Characteristics of Fuchs Endothelial Corneal Dystrophy in Thai Patients: A Retrospective Cohort in a Tertiary Referral Center - Wannapanich T; Puangsricharern V; Satitpitakul V; Kittipibul T; Suphapeetiporn K (Clinical Ophthalmology)
Trakanta Wannapanich,1,2 Vilavun Puangsricharern,1,3 Vannarut Satitpitakul,1,3 Thanachaporn Kittipibul,1,3 Kanya Suphapeetiporn4– 6 1Center of Excellence for Cornea and Stem Cell Transplantation, Department of Ophthalmology, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 2Excellence Center for Cornea and Stem Cell Transplantation, Department of Ophthalmology, King Chulalongkorn Memorial Hospital, Thai Red Cross Society, Bangkok, Thailand; 3Department of Ophthalmology, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 4Department of Pediatrics, Faculty of Medicine, Chulalongkorn University Bangkok, Bangkok, Thailand; 5Excellence Center for Genomics and Precision Medicine, King Chulalongkorn Memorial Hospital, The Thai Red Cross Society, Bangkok, Thailand; 6Center of Excellence for Medical Genomics, Department of Pediatrics, Faculty of Medicine, Chulalongkorn University, Bangkok, ThailandCorrespondence: Vilavun Puangsricharern, Department of Ophthalmology, Faculty of Medicine, Chulalongkorn University, 1873, Rama 4 Road, Pathumwan, Bangkok, 10330, Thailand, Email vilavun@hotmail.com Kanya Suphapeetiporn, Department of Pediatrics, Faculty of Medicine, Chulalongkorn University, 1873, Rama 4 Road, Pathumwan, Bangkok, 10330, Thailand, Email kanya.su@chula.ac.thPurpose: To describe the demographic profile, clinical characteristics, and treatment trends of Fuchs endothelial corneal dystrophy (FECD) in Thai patients, reflecting the evolving landscape of corneal transplantation in this region.Patients and Methods: This retrospective cohort study included 900 patients (1,743 eyes) diagnosed with FECD at a tertiary referral center in Thailand between January 2017 and June 2023. Demographic, clinical, and surgical data were analyzed, focusing on best-corrected visual acuity (BCVA), central corneal thickness (CCT), endothelial cell density (ECD), surgical interventions, and graft survival rate.Results: The mean age was 63.9 years, with 77.2% of patients being female. Most eyes were classified as Adamis grade I (83.7%). Diabetes mellitus and hypertension were prevalent in 17.4% and 38.6% of patients, respectively. The rate of corneal transplantation was 8.1%, with DMEK accounting for 69.3% of transplants. Graft survival rates were 94.3% at 1 year and 76.2% at 5 years. The average post-operative ECD declined from 1667.8 ± 668.0 cells/mm² at 1 year to 1140.7 ± 684.4 cells/mm² at 5 years. Cataract surgery was performed in 20.4% of phakic eyes, with only 2.2% requiring corneal transplantation within five years.Conclusion: FECD in Thailand, as reflected by this large cohort, predominantly presents at an early stage, allowing for conservative management. The growing use of DMEK highlights the shift towards less invasive procedures, mirroring global trends in Southeast Asia. These findings emphasize the importance of advancing surgical techniques and improving eye banking practices in the region.Keywords: corneal transplantation, endothelial keratoplasty, DMEK, keratoplasty trends, eye banking